Traumas of Roots and Extinction in the 20th Century Literature of Empire: The Mirror Principle in Marguerite Duras’ India Cycle (1964-71) and Ahmed Ali’s Twilight in Delhi (1940) - Fernée, Tadd Graham (English Studies at NBU, 2020)
This article comparatively analyses Marguerite Duras’ India Cycle and Ahmed Ali’s Twilight in Delhi. A Mirror Principle centres on ’emptiness’, synthesising elements of Marxism and Buddhism. A new optic is created for understanding 1930s Indian nationalism, including Dalit and national leader Ambedkar, Tagorian ’composite culture’, Mohammed Iqbal, and Islam and gender in northern India. The Mirror Principle juxtaposes Heideggerian ’repetition’ and Marxian ’dialectics’ as divergent anti-colonial paths. Duras and Ali are linked by a common Proustian problematic of memory and ephemerality. They revolutionize the Proustian tradition to create a new literary genre in oneiric socialism. The article analyses trauma, in the French Resistance and the 1857 rebellion, and literary reconstructions of traditional roots in their wake, with differing nation-making ramifications.